An Image Smearing Technique to Improve Pigeon Hole Imaging (PHI) (Bangladesh Journal of Medical Physics, 2013)
This new imaging modality arises as an extension of the 6-electrode Focused Impedance Method (FIM) developed in our laboratory earlier. Current is driven through two concentric pairs of orthogonally placed electrodes while several potential electrodes are located along a diagonal centrally. Through a combination of current drives and potential measurements across adjacent diagonal electrodes, it is possible to obtain admittance sums along the rows and columns of a square matrix formed by these diagonally placed potential electrodes. Through simple backprojection along the rows and columns it is possible to reconstruct a crude image in a square matrix form. Due to its resemblance, the name Pigeon Hole Imaging (PHI) has been coined. The concept has been experimentally tested to identify the location of a single target object in a background of uniform conductivity in 2D and 3D phantoms, in 2x2 and 6x6 matrix formations respectively. Taking the highest pixel to represent the object position the images were correct in all the pixels of the 2x2 image but in only 16 of the 36 pixels adjacent to the diagonal electrodes in the 6x6 image. However, a systematic pattern of image shift was observed in most of the other pixels in the latter, based on which a set of rules were made to correct the image in another 14 pixels. Thus excepting the furthest 6 pixels, correct image could be obtained in all 30 pixels. Thus PHI will be useful in locating exact positions of single target objects simply. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14673 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 11-20